The Influence of Work Discipline and Organizational Culture on Employee Performance of PT. Angkasa Pura Solusi Kota Tangerang - Arsando, Fellix Barnast; Sutarto, Bambang (Pascasarjana Universitas Pasundan, 2024)
The purpose of this study was to determine the effect of work discipline and organizational culture on the performance of employees of PT Angkasa Pura Solusi, Tangerang City. The method used is quantitative. The sampling technique used saturated sampling of 80 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that work discipline has a significant effect on employee performance with a determination coefficient value of 41.2% and the hypothesis test is obtained t count > t table or (7.387 > 1.991). Organizational culture has a significant effect on employee performance with a coefficient of determination of 41.5% and the hypothesis test is obtained t count > t table or (7.445 > 1.991). Work discipline and organizational culture simultaneously have a significant effect on employee performance with the regression equation Y = 9.054 + 0.373X1 + 0.418X2. The coefficient of determination is 56.5% while the remaining 43.5% is influenced by other factors. Hypothesis testing obtained F count > F table or (49,981 > 2,720). this job work discipline and organization culture together have a positive and significant impact on employees the west of PT Angkasa Pura Solusi Tangerang City.